Pemberdayaan UMKM Batik dalam Rangka Meningkatkan Daya Saing Produk Unggulan Daerah di Desa Ngentrong Kecamatan Karangan Kabupaten Trenggalek - Setyawati, Hafidha Putri; Hardjati, Susi (Universitas Batanghari Jambi, 2024)
Trenggalek Regency has typical batik with the main motif of clove flowers. Currently the batik center in Ngentrong Village is the most famous center in Trenggalek Regency which is currently experiencing many problems regarding the development of existing Human Resources. This research aims to determine the empowerment of Batik Micro, Small and Medium Enterprises (MSMEs) in order to increase the competitiveness of regional superior products in Ngentrong Village, Karangan District, Trenggalek Regency. This research uses a qualitative approach with descriptive methods. The focus of this research uses the empowerment aspect theory, namely enabling, empowering, and protecting. The data collection techniques used in this research are interviews, observation, and documentation. The data analysis techniques used are data collection, data condensation, data presentation, and drawing conclusions and verification. In this research, the validity tests used are the credibility test, dependability test and confirmability test. The results of this research found that when viewed from the enabling, empowering and protecting aspects as a whole, it can be stated that the empowerment of Batik Micro, Small and Medium Enterprises (MSMEs) in order to increase the competitiveness of regional superior products in Ngentrong Village, Karangan District, Trenggalek Regency has not yet been achieved. done optimally.